2022
DOI: 10.3389/fphar.2022.907133
|View full text |Cite|
|
Sign up to set email alerts
|

Receptor of Advanced Glycation End Products Deficiency Attenuates Cisplatin-Induced Acute Nephrotoxicity by Inhibiting Apoptosis, Inflammation and Restoring Fatty Acid Oxidation

Abstract: Cisplatin is a widely used and potent anti-neoplastic agent, but severe and inescapable side effects in multiple normal tissues and organs limit its application, especially nephrotoxicity. Molecular mechanisms of cisplatin nephrotoxicity involve mitochondrial damage, oxidative stress, endoplasmic reticulum stress, inflammation, apoptosis, necroptosis, etc. Receptor of advanced glycation end products (RAGE) is a multiligand pattern recognition receptor, engaged in inflammatory signaling and mitochondrial homeos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…KEGG analysis emphasizes pathways that are usually activated in hypoxic environments and increased oxidative stress, such as the AGE-RAGE signaling pathway, which is usually activated in diabetes [27]. On the other hand, inhibition of RAGE has been recently reported as a promising approach to alleviate nephrotoxicity induced by CP [28]. Furthermore, PV was identified as a lead compound that could inhibit RAGE [29,30], which confirms the accuracy of our network pharmacology results.…”
Section: Discussionsupporting
confidence: 83%
“…KEGG analysis emphasizes pathways that are usually activated in hypoxic environments and increased oxidative stress, such as the AGE-RAGE signaling pathway, which is usually activated in diabetes [27]. On the other hand, inhibition of RAGE has been recently reported as a promising approach to alleviate nephrotoxicity induced by CP [28]. Furthermore, PV was identified as a lead compound that could inhibit RAGE [29,30], which confirms the accuracy of our network pharmacology results.…”
Section: Discussionsupporting
confidence: 83%
“…The discovery that lipid biology was differentially impacted by RAGE signaling supports a previously seen link between RAGE and fatty acid metabolism [30]. For instance, Wang et al demonstrated that the loss of RAGE differentially impacted apoptosis and inflammation, which resulted in restored fatty acid oxidation [31]. Further, clarifying a link between RAGE signaling and the elaboration of adipocytokines further implicates RAGE in recently researched axes of metabolic syndrome, cancer, and obesity.…”
Section: Discussionmentioning
confidence: 62%
“…WB analysis was performed as previously described 26 . Briefly, cells or tissues were lysed in RIPA buffer containing protease and phosphatase inhibitors.…”
Section: Western Blot (Wb) Analysismentioning
confidence: 99%